Gênero e diversidade na escola: reflexões acerca da formação continuada sobre assuntos da diversidade sexual - Rossi, Célia Regina [UNESP]; Vilaronga, Carla Ariela Rios; Garcia, Osmar Arruda; Lima, Maria Teresa Oliveira [UNESP] (My University, 2012)
This article aims to discuss reports brought by the teacher the early years of public school in the training course in Gender and Diversity in School (GDS), with regard to the prejudices of gender and sexual diversity. The GDS training course was offered in 2009 and 2010, by the Open University of Brazil (UAB), in cooperation agreement with the Universidade Estadual Paulista (Unesp). In São Paulo the training centers were distributed in 09 municipalities. The course GDS was inserted in the modality teacher continuing education elementary education from the public schools, in the semipresencial way, and it was divided into five thematic modules: diversity, gender, sexuality and sexual orientation, race / ethnicity. In this article, we present the analysis of the memorials written by / the teacher / participants of the 1st GDE course, polo Jau, in the state of São Paulo, that link the learning which was experienced in the course. Were obtained reports about conflicts arising from the dissonance of personal beliefs and professional responsibilities; involvement of the life’s history of the teacher in his performance in the school (subjectivities); transposition of conceptual errors built out of school, between other aspects. It could be observed that the course has destabilized these teachers with some questions about their certainties. The difficulty in changing and transforming concepts and prejudices about sexual and gender diversity was clarified during the course. The course enabled the educators the contact with contemporary questions, reflect on their attitudes and conceptions of education, which can help to transform their practices in school, providing new perspectives on the issue of sexuality

Este artigo objetiva problematizar relatos dos/as professores/as dos anos iniciais da escola pública, no âmbito da formação no curso Gênero e Diversidade na Escola (GDE), quanto aos preconceitos de gênero e diversidade sexual. O curso foi oferecido em 2009 e 2010, pela Universidade Aberta do Brasil (UAB), em convênio com a Universidade Estadual Paulista (Unesp). No Estado de São Paulo, os polos de formação foram distribuídos em nove municípios. O curso GDE se inseriu na modalidade de formação continuada de professores/as da Educação Básica de escolas públicas, de forma semipresencial, e foi dividido em cinco módulos temáticos: diversidade, gênero, sexualidade e orientação sexual, raça/etnia. Neste artigo apresentamos as análises dos memoriais escritos pelos/as professores/as participantes do 1º curso GDE, do polo de Jaú, interior do Estado de São Paulo, que apontam o aprendizado vivenciado no curso. Obtiveram-se relatos sobre conflitos resultantes da dissonância das crenças pessoais e das responsabilidades profissionais; o envolvimento da história de vida dos/as professores/as em sua atuação escolar (subjetividades); a transposição de equívocos conceituais construídos fora da escola para dentro, entre outros aspectos. Foi possível perceber que o curso conseguiu desestabilizar esses/as professores/as, com questionamentos de algumas certezas. Foi explicitada pelo grupo participante a dificuldade em mudar e transformar conceitos e preconceitos sobre diversidade sexual e gênero. O curso possibilitou aos educadores/as entrar em contato com questões contemporâneas, refletir sobre suas posturas e concepções de educação, o que poderá contribuir para transformar suas práticas na escola, possibilitando novos olhares sobre a questão da sexualidade.
Gender and diversity in school: reflections on the continuing education on matters of sexual diversity
Keywords: Sexuality; Gender; Teacher training; Sexual diversity; Sexualidade; Gênero; Formação docente; Diversidade sexual; Preconceito